Harga Diri dan Perilaku Agresif serta Hubungannya dengan Kemarahan pada Remaja - Mayangsari, Agnes Mariana (Universitas Muria Kudus, 2022)
This study aims to determine the significance of the relationship between self-esteem and anger in adolescents at the Woro Wiloso Orphanage, Salatiga, and the significance of the relationship between aggressive behavior and anger in adolescents at the Woro Wiloso Orphanage, Salatiga. Anger is the cause of the emergence of aggressive behavior in a human being. Therefore, aggressive behavior and anger are two things that are related to each other. This will be exacerbated if a person's self-esteem is disturbed. Referring to the results of data analysis, obtained a significant relationship between self-esteem and anger of 0.000 0.05 with a negative correlation coefficient of -0.568. Furthermore, it is also known that the significance of the relationship between aggressive behavior and anger is 0.000 0.05 with a correlation coefficient of 0.797. So the conclusion, there is significant relationship between self-esteem and anger, and there is significant relationship between aggressive behavior and anger.